Impact of age and agility performance level on the disjunctive reaction time of soccer goalkeepers - Obetko, M.; Perácek, P.; Šagát, P.; Mikulic, M. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2019)
The soccer goalkeeper's reaction speed to stimulus is essential for the overall success rate of goalkeepers in soccer. Our research was aimed at finding out the impact of age and agility performance level on the length of the disjunctive reaction time of elite goalkeepers in Slovakia. The research group was comprised of 24 goalkeepers of two Slovak soccer clubs (in group A were elite players and in group B sub-elite players). To gain the research data, the disjunctive reaction time was measured using the Fitro Agility Check device. The acquired results were statistically evaluated using the Mann-Whitney U-Test and Cohen's "d". The impact of age (n.s) and performance level (n.s) on the length of the disjunctive reaction time of goalkeepers was not statistically confirmed. However, the substantive and logical significance showed that the best goalkeepers achieved a considerably shorter time of disjunctive reaction time to the set stimulus (difference - 20 %).